Efektifitas Model Gamifikasi dalam Meningkatkan Keterlibatan Motivasi Belajar STEAM di Usia Dini - Anik Nurul Hidayah; Dedi Kuswandi; Pramono Pramono (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2026)
Early childhood learning should be grounded in the principle of learning through play, which emphasizes active engagement and direct experience. However, learning practices in early childhood education institutions are still dominated by conventional, teacher-centered approaches, resulting in low levels of children’s interest, motivation, and learning engagement.  This study aims to develop a gamification-based project learning model incorporating STEAM (Science, Technology, Engineering, Art, and Mathematics) and to test its effectiveness in increasing children's motivation and engagement in learning.. This research employed a Research and Development (R&D) method using the ADDIE procedure, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were Group B children at TK PKK 4, Pasuruan Regency. Data were collected through observation, interviews, and documentation. The feasibility of the learning model was evaluated through validation by subject matter experts, instructional design experts, and media experts. The effectiveness of the model was tested using a pre-experimental design by analyzing the improvement scores through N-Gain based on pretest and posttest results of children’s motivation and learning engagement. The results showed that the gamification-based STEAM learning model was valid and feasible for use, with subject matter expert validation reaching 79.4% (valid) and instructional design expert validation reaching 96.6% (very valid), along with media design revisions based on expert feedback. The implementation of gamification elements such as missions, points, challenges, and badges effectively increased children’s interest and active participation in learning activities. The N-Gain score of 0.5 indicated a moderate improvement in children’s motivation and learning engagement. Therefore, the gamification-based STEAM learning model is effective in enhancing motivation and learning engagement in early childhood education.